Ambient carbon monoxide and cardiovascular-related hospital admissions: A time-series analysis - Taheri, Marzieh; Nouri, Fatemeh; Ziaddini, Mahdi; Rabiei, Katayoun; Pourmoghaddas, Ali; Shariful Islam, Sheikh Mohammed; Sarrafzadegan, Nizal (Frontiers in Physiology, 2023)
Although plenty of studies have investigated the association between air pollutants and cardiovascular disease (CVDs) in recent years, a lack of evidence exists regarding Carbon monoxide (CO) exposure, especially in the eastern Mediterranean's polluted regions. In this study, we aimed to evaluate the short-term effect of CO exposure on daily CVDs hospital admissions in Isfahan, a major city in Iran. Our data was excerpted from the CAPACITY study. This study extracted daily CVDs hospital admissions in Isfahan from March 2010 to March 2012. The 24-hours mean CO concentrations was obtained from 4 local monitoring stations. In a time-series framework, the association between CO and daily hospitalizations for total and cause-specific CVDs for adults (ischemic heart disease (IHD), heart failure (HF), and cerebrovascular disease) was conducted using Poisson (or negative binomial) regression, controlling for holidays, temperature, dew point, and wind speed, considering different lags and mean lags of CO. The robustness of the results was checked via Two- and multiple-pollutant models. Stratified analysis was also conducted for age groups (18-64 years and ≥65 years), sex, and seasons (cold and warm). The current study incorporated a total of 24335 hospitalized patients entailing 51.6% male, with a mean age of 61.9 ± 16.4. The mean CO concentration was 4.5±2.3 mg/m³. For a 1 mg/m3 increase in CO, we found a significant association with the number of CVD hospitalizations. The largest adjusted percent change for HF was seen in lag0, 4.61% (2.23,7.05), while for total CVDs, IHD, and cerebrovascular diseases occurred in mean lags2-5, 2.31% (1.42,3.22) and 2.23% (1.04,3.43), 5.70% (3.59,7.85), respectively. Results were robust in two- and multiple-pollutant models. Although the associations changed for sex, age groups, and seasons, remained significant except for IHD and total CVD in the warm season, and in HF for the young and cold seasons. Additionally, exposure-response relationship curve of the CO concentrations with total and cause-specific CVD admissions were explored which showed non-linear relationships for IHD and total CVDs. Our results showed that exposure to CO contribute to an increase in the number of CVD hospitalizations. The associations were not independent of age groups, season and sex.